ONLINE VIDEO GAME: THE INNOVATION OF DENTAL HEALTH EDUCATION TOOLS FOR CHILDREN DURING COVID-19 PANDEMIC - Yufitri Mayasari; Belanita Belanita; Elin Hertiana (Universitas prof. Dr. Moestopo (Beragama), 2021)
COVID-19 has presents unprecedent challenge in many aspects of dentistry include oral health promotion. Oral health promotion is recognized an essential component to prevent the oral disease during pandemic. As we know, dental caries is the most common dental and oral health problem suffered by children due to behaviour of maintaining oral health which is often ignored and based on poor knowledge. One way to change the behaviour is through health education using the right media or tool to make it more effective and efficient. Research objectives are to explain knowledge disparity of dental and oral health among students before and after education video game. Pre experiment study with one group pretest until post-test design was taken from a sample of fourth-grade students of SDN 03 Pesanggrahan. The sampling technique was total sampling with a sample size of 66 respondents. Kolmogorov Smirnov test was used for normality test and Wilcoxon test was used for analysing the data. The result obtained from the statistical test of the differences in dental and oral health knowledge among students before and after education through a video game was p-value = 0.001.